Fundamentals of Occupational Therapy : an Introduction to the Profession. - Hattjar, Bernadette (SLACK, Incorporated, 2018)
Fundamentals of Occupational Therapy: An Introduction to the Profession is a comprehensive, introductory text that provides first year students with foundational knowledge of occupational therapy as a profession and the construct of occupation. Due to the broadness of the profession this text identifies basic concepts and areas to novice students and helps inform them of the topics and components they will come across later in their studies.